Adaptive Educational Management in Building an Anti-Bullying Environment and Improving Student Learning Quality - Robian Henri; Sri Handayani (Dinasti Publisher, 2025)
Bullying in elementary schools seriously harms students' mental health and learning quality. Schools with limited resources need an adaptive management model to tackle this effectively. This research stems from the gap between ideal anti-bullying policies and real-world challenges. It describes and analyzes adaptive education management at SDN 036 Ujungberung and SDN Cibodas 01 to handle bullying and improve student learning. This research employs a qualitative approach with a case study method and applies the management framework (Planning, Organizing, Actuating, and Controlling) as its theoretical basis. Data were collected through in-depth interviews, participatory observation, and documentation studies. The findings indicate that at SDN 036 Ujungberung and SDN Cibodas 01 implements a contextual, flexible, and collaborative model of adaptive education management. (1) Planning is conducted participatively by establishing a Prevention and Handling of Violence Team (TPPK) and designing realistic programs tailored to resource limitations. (2) Organization is dynamic, with all teachers actively involved in prevention and supervision. (3) Implementation is humanistically integrated into routine school activities through education, habituation, and direct mediation. (4) Controlling and follow-up are carried out continuously through simple yet regular evaluations, the results of which are used for tangible program improvements. The primary challenge of limited human resources is overcome through collaboration and role flexibility. In conclusion, contextual and responsive adaptive management builds safe, inclusive, character-focused school cultures. It successfully cuts bullying and boosts learning quality, even in resource-poor settings.